Entranced Glauber: Time as social dimension in Paulo Martins’s poetry - Barrós, Manuel (2018)
In this paper I analyse the time as a social dimension in the aesthe- tic of Terra em transe (1967) through Paulo Martin’s poetry, Glauber Rocha’s alter ego. From Brecht’s theoretical ideas, I propose that verbal poetical language was very important because through its re- presentations of time I can study its lyrical relevance: its dramatic quality and its capacity to show the emotional transitions and political movements of the protagonist. At the moment I analyse its aesthetics specificity, this one makes me think in its complex relations with other artistic languages involved on the film and its contributions to achieve the film in the Brazilian military  dictatorship context (1964-1985).